Evaluation of permanent deformation of CRM-reinforced SMA and its correlation with dynamic stiffness and dynamic creep - Mashaan, Nuha Salim; Karim, Mohamed Rehan (Hindawi Publishing Corporation, 2013)
Today, rapid economic and industrial growth generates increasing amounts of waste materials such as waste tyre rubber. Attempts to inspire a green technology which is more environmentally friendly that can produce economic value are a major consideration in the utilization of waste materials. The aim of this study is to evaluate the effect of waste tyre rubber (crumb rubber modifier (CRM)), in stone mastic asphalt (SMA 20) performance. The virgin bitumen (80/100) penetration grade was used, modified with crumb rubber at four different modification levels, namely, 6, 12, 16, and 20 by weight of the bitumen. The testing undertaken on the asphalt mix comprises the indirect tensile (dynamic stiffness), dynamic creep, and wheel tracking tests. By the experimentation, the appropriate amount of CRM was found to be 16 by weight of bitumen. The results show that the addition of CRM into the mixture has an obvious significant effect on the performance properties of SMA which could improve the mixture's resistance against permanent deformation. Further, higher correlation coefficient was obtained between the rut depth and permanent strain as compared to resilient modulus; thus dynamic creep test might be a more reliable test in evaluating the rut resistance of asphalt mixture. Â© 2013 Nuha Salim Mashaan and Mohamed Rehan Karim.